CYP2C19 genotype variability in patients with refractory gastroesophageal reflux after per-oral endoscopic myotomy (POEM) - Perbtani, Yaseen B.; Westerveld, Donevan R.; Yang, Dennis J.; Draganov, Peter V. (Endoscopy International Open, 2021)
Background and study aims Symptomatic gastroesophageal reflux is a recognized potential adverse event following peroral endoscopic myotomy (POEM). Proton pump inhibitors (PPIs) are an effective first-line therapy; although their efficacy can be affected by genotype cytochrome P450 2C19 (CYP2C19) variability leading to enhanced clearance of PPIs. The aim of our study was to evaluate the incidence of CYP2C19 genotype variability in POEM patients with refractory gastroesophageal reflux symptoms.Patients and methods This was a single-center, prospective, cohort study of consecutive POEM cases during a 7-year study period (2013–2020). Reflux symptoms were assessed with the validated gastroesophageal reflux disease questionnaire (GerdQ) and objective pH testing after POEM. CYP2C19 genotype testing was obtained in all patients with refractory gastroesophageal reflux disease (GERD) symptoms, defined as an abnormal pH study and GerdQ score ≥ 8 while on PPIs twice daily.Results POEM was performed in 325 consecutive patients (48.3 % female; mean age 57 years) during the study period. Twenty patients (6.8 %) had PPI-refractory, post-POEM gastroesophageal reflux based on their GerdQ score (median 9, range 8–11) and abnormal pH studies. CYP2C19 genotype testing identified 55 % (11/20) of these patients as being rapid metabolizers. Out of these, 9 (82 %) had improvement in clinical GERD symptoms after changing to a PPI less affected by CYP2C19 pharmacogenetics.Conclusions Post-POEM, PPI-refractory GERD is rare. As shown in this study, rapid metabolizers commonly respond by changing to a PPI less affected by CYP2C19 pharmacogenetics, thereby reducing the risk of long-term consequences from GERD and unnecessary anti-reflux surgery.